Gelir hareketliliği eşitsizlikleri azaltabilir mi? Türkiye örneği - Aytekin Güven; Başak Dalgıç; Aysit Tansel (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
– Increasing income inequality has made economists focus on income mobility issue which enables individuals to relocate their income position up to higher income groups. Income mobility and its effects on inequalities have begun to be investigated following 2000s and rather for developed countries while there are only a limited number of studies to reach a general conclusion regarding the issue. This study aims to contribute to the literature by analyzing income inequality and income mobility together for a developing country Turkey which is one of the countries having most unequal income distributions. The results of this study can be summarized as follows; i) income mobility increases over time but this mobility raises income inequality instead of reducing it. ii) the individuals at the two tails of the distribution are more mobile with respect to the ones in the middle. iii) 30 percent of the individuals at the lowest income group become unemployed while only 1.5 percent of them move up to the highest income group in the considering sub-periods.
Keywords: D31; D63; J60; 330; Income Mobility; Income Inequality; Turkey